The Influence of E-Money Usage Frequency and Understanding of Sharia Principles on Millennial Consumptive Behavior - Merry; Nur Fitri Hidayanti; Zaenafi Ariani; Mukhlishin (Universitas Bangka Belitung, 2025)
The utilization of electronic money (e-money) has significantly increased in the era of digitalization, altering the consumption patterns of Muslim millennials in Mataram. This study aims to investigate the impact of the frequency of e-money usage and the level of understanding of Sharia principles on Sharia-compliant consumption behavior. Employing a quantitative research design, the study surveyed 93 respondents selected through simple random sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The findings reveal that the frequency of e-money usage exerts a positive and statistically significant influence on consumption behavior aligned with Sharia principles, exhibiting a coefficient of 54.4% and a significance value of 0.00. Furthermore, the understanding of Sharia values demonstrates a positive effect of 28.3%, with a significance value of 0.013. Collectively, these two variables exert a robust influence on Sharia-oriented consumption behavior, as indicated by an F value of 51.99 and an R-squared value of 52.6%. These results suggest that an increased frequency of e-money usage, coupled with a deeper understanding of Sharia principles, corresponds to more ethical and balanced consumption behavior among Muslim millennials. Consequently, it is imperative to enhance digital literacy in conjunction with strengthening Sharia financial literacy, ensuring that the adoption of financial technology aligns with the objectives of Maqashid al-Syariah in fostering economic welfare and accountability in the digital age.